Speech by the Hon'ble Enche Ooh Chooi Cheng J.P Deputy Chief Minister at the Official Opening Of An Art exhibition of recent works by the Chia Yu chian,brothers & sisters on Saturday 15th January, 1972 at 2.30 p.m. at The Penang Library Penang. - Ooh, Choi Cheng (1972)
It gives me great pleasure to be present here to-day on the occasion of this exhibition of recent works by the Chia family.